(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-94-103 The article analyzes the ancient motifs in specific stories, lectures and letters of the Anglo-American writer Lafcadio Hearn (1850–1904), defines their role in the work of the writer. The author studies the relationship between the cultures of Ancient Greece and Japan in the writer’s submission, studies the following topics: metamorphoses, insect poetry. Antique references help to reveal the similarities between East and West, L. Hearn finds a common basis for the two worlds: ancient times. Key words: Ancient Greece, Japan, myth, metamorphoses, insect poetry, sacred, L. Hearn.